2016
DOI: 10.1155/2016/2680409
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Rosemary (Rosmarinus officinalis) Diterpenes for Alzheimer’s Disease

Abstract: Rosemary (Rosmarinus officinalis L.) is one of the most economically important species of the family Lamiaceae. Native to the Mediterranean region, the plant is now widely distributed all over the world mainly due to its culinary, medicinal, and commercial uses including in the fragrance and food industries. Among the most important group of compounds isolated from the plant are the abietane-type phenolic diterpenes that account for most of the antioxidant and many pharmacological activities of the plant. Rose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(118 citation statements)
references
References 169 publications
(159 reference statements)
0
113
0
5
Order By: Relevance
“…Carnosic acid, which was first Terminalia chebula (T. chebula -secretase which is one of the major proteolytic enzymes that process amyloid precursor protein. The mechanism behind its neuroprotective actions involves not only inhibition of AChE and β-amyloid deposits as well as antiBuChE (butyrylcholinesterase) activity [81]. Apart from above activities, it possesses cytoprotective, anti-apoptotic and antiinflammatory activities that also add on to its neuroprotective mechanism [82].…”
Section: Rosmarinus Officinalismentioning
confidence: 99%
“…Carnosic acid, which was first Terminalia chebula (T. chebula -secretase which is one of the major proteolytic enzymes that process amyloid precursor protein. The mechanism behind its neuroprotective actions involves not only inhibition of AChE and β-amyloid deposits as well as antiBuChE (butyrylcholinesterase) activity [81]. Apart from above activities, it possesses cytoprotective, anti-apoptotic and antiinflammatory activities that also add on to its neuroprotective mechanism [82].…”
Section: Rosmarinus Officinalismentioning
confidence: 99%
“…A recent review of Rosemary explains the therapeutic role it may play to aid those with Alzheimer's disease [4]. Various studies have demonstrated that Rosemary's bioactives support brain health and may have a role in enhancing cognitive function [37].…”
Section: Discussionmentioning
confidence: 99%
“…This plant is used around the world for its culinary and medicinal uses, including use in both the food and fragrance industries. Rosemary is known for its powerful antioxidant properties and biologically active medicinal value [4]. The leaves are commonly used as a food additive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, establishing their multifunctional role to tackle diseases like diabetes/obesity along with many other complex diseases (e.g., Alzheimer's disease) have been the focus of our research in recent years. Many review articles substantiating such drug-target approaches for complex diseases have also been published [11][12][13][14][15][16][17][18][19][20][21]. Interestingly, many plant polyphenols are not only working through multifunctional mechanisms but also synergise to produce more pronounced effects.…”
Section: Smart Drugs For Complex Diseasesmentioning
confidence: 99%